PLOT IN BAZ LUHRMANNâ€™S THE GREAT GATSBY MOVIE - Putri, Made Gyan Vigyani (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThis study aims to analyze plot as one of the intrinsic elements of literary work in the formof a film entitled â€œThe Great Gatsbyâ€. The data for this study came from Baz Luhrmann'sfilm, which was released in 2013. The approach of this study was the descriptive qualitativemethod. There are several questions that researcher wants to find, they are focused on theplot laws and structure of plot is applied in the movie proposed by Kenney in his bookentitled How to Analyze Fiction (1966). The findings of the research show that there are sixsections for plot laws, which include plausibility, surprise, suspense, plot and unity, plot asunity, and plot as expression. only the subplot is not found in the movie. For the plotstructure, there are five plot stages proposed by Kenney, which consists of the beginning ofthe story, the middle of the story which is divided into three parts, namely conflict,complication and climax.Keywords: analysis plot, literature, plot laws, structure of plotABSTRAKStudi ini bertujuan untuk menganalisis plot sebagai salah satu elemen intrinsik dari karyasastra dalam bentuk film berjudul "The Great Gatsby". Data untuk penelitian ini berasaldari film Baz Luhrmann, which dirilis pada tahun 2013. Pendekatan penelitian ini adalahmetode kualitatif deskriptif. Ada beberapa pertanyaan yang ingin ditemukan peneliti,mereka berfokus pada hukum plot dan struktur plot yang diterapkan dalam film yangdiusulkan oleh Kenney dalam bukunya yang berjudul How to Analyze Fiction (1966).Temuan penelitian the menunjukkan bahwa ada enam bagian untuk hukum plot, yangmeliputi masuk akal, kejutan, ketegangan, plot dan persatuan, plot sebagai kesatuan, danplot sebagai ekspresi. Untuk penataan plot, ada lima tahap plot yang diusulkan oleh Kenney,yang terdiri dari awal cerita, tengah cerita yang dibagi menjadi tiga bagian, yaitu konflik,komplikasi dan klimaks.Kata kunci: plot analisis, literatur, hukum plot, struktur plot